Improvement of polysaccharide and triterpenoid production of Ganoderma lucidum through mutagenesis of protoplasts. Issue 2 (3rd March 2016) - Peng, Ren; Fu, Yongze; Zou, Jiao; Qiu, Hai; Gan, Lianting; Yi, Hailin; Yao, Ruyuan; Luo, Xingyuan
ABSTRACT: Ganoderma lucidum is a traditional medicinal macrofungus in China, which has two kinds of key bioactive compounds – polysaccharides and triterpenoids. To improve the polysaccharide and triterpenoid production from G. lucidum, the preparation and regeneration conditions of protoplasts were optimized. This was done by systematic trials with various parameters, and protoplast mutation was subsequently performed. A mycelium that was cultivated for seven days and treated with 0.33 mL of 1% snailase and 0.66 mL of 0.5% cellulase solution for 2.5 h at 30 °C in the presence of osmotic pressure stabilizer mannitol (0.5 mol/L), had the best conditions, in which the resultant protoplasts were 6.40 × 10 5 /mL and the regeneration rate was 6.25%. The resultant protoplasts were subjected to subsequent mutation by lithium chloride or by the combination of lithium chloride and Triton X-100. The highest yields of intracellular polysaccharide and triterpenoid in two mutant strains were 37.50 and 40.81 mg/g, which were increased with 568.45% and 373.43%, respectively, as compared to the original strain. Furthermore, the yields of intracellular polysaccharides and triterpenoids in the second generation and the third generation of the mutants were comparable to that of the first generation, which showed genetic stability of the mutants for the production of polysaccharides and triterpenoids.